2020
DOI: 10.1186/s12955-020-01425-w
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the content and face validity of preference-based measures within the context of dementia

Abstract: Background Assessing the cost-effectiveness of interventions for people with dementia, based on cost per quality-adjusted life years (QALYs) gained, requires that the measures used to derive QALYs are preference-based whilst also being valid, feasible to use, comprehensible and acceptable for people with dementia. The aim of this study was to assess the content and face validity of six preference-based measures (PBMs) within the context of dementia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…These issues have been noted in previous content validation studies of the EQ-5D-3L in older populations. 13,39 The ONS-4 worthwhile item was interpreted in different ways, to mean worthwhile either to themselves or to society, consistent with findings from a previous content validation. 44 Response option selection issues were also seen for the SF-12v2 moderate activities item.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…These issues have been noted in previous content validation studies of the EQ-5D-3L in older populations. 13,39 The ONS-4 worthwhile item was interpreted in different ways, to mean worthwhile either to themselves or to society, consistent with findings from a previous content validation. 44 Response option selection issues were also seen for the SF-12v2 moderate activities item.…”
Section: Discussionsupporting
confidence: 75%
“…These themes closely reflect the World Health Organization definition of healthy aging, which centers on maintaining functional ability to enable the well-being of older adults 12 and key themes identified in the literature. 2,3,[37][38][39] This provides support that these themes are generalizable to older adults more broadly. Developers of PROMs for use in older adults should consider these core domains.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…59 At the same time, several economic evaluations in care home populations have been published that show the EQ-5D can be used in this population 20,60 and may be more responsive than the DEMQOL-P-U. 59 Recently, however, a qualitative study comparing six preference-based measures (in terms of face and content validity) in the context of dementia found that no single instrument was favoured, 61 such that choice of a preference-based measure remains on the research agenda.…”
Section: Strengths and Limitations Of The Economic Evaluationmentioning
confidence: 99%